Fermentation in fish and by-products processing: an overview of current research and future prospects. (February 2020) - Marti-Quijal, Francisco J; Remize, Fabienne; Meca, Giuseppe; Ferrer, Emilia; Ruiz, María-José; Barba, Francisco J
Highlights: Fish by-products (FBP) fermentation allows obtaining high-added value compounds. Fermentation is a useful tool to obtain bioactive peptides from FBP. Fermentation as a strategy to produce antifungal/antimicrobial compounds from FBP. Fermentation can help reducing the environmental problem caused by fish waste. Abstract : Fish industry has been growing continuously over the last decades and generates huge amounts of by-products. These by-products come from fish head, skin, bones, thorns, and viscera. Part of them are processed for feed, collagen and oil production, and to a lesser extent to produce biofuels and fertilizers, but many other high-value bioactive compounds can be recovered. Fish fermentation, which is traditionally used to increase fish shelf-life, results into the formation of bacteria metabolites of interest. Applied to by-products, fermentation increases the quality of protein hydrolysates, oil and produces antioxidant compounds. This technology, which is safe, environmental-friendly and poor energy consuming, presents advantages for future applications.